Creating industry driven sustainable technical graduates: A case from Malaysia - Rajadurai J.; Sapuan N.M.; Daud S.; Abidin N. (American Scientific Publishers, 2023)
Higher Education Institutions (HEIs) are faced with several challenges in producing marketable technical graduates given the present highly competitive and volatile employment market. Employers have expressed concerns that these graduates lack the relevant academic qualifications, skills, abilities and attitudes. The main aim of this study, therefore, is to investigate the gap between industry expectations for these graduates and their actual performance when employed by industry. Industry expectations and graduate performances were investigated in four dimensions, namely knowledge, skills, abilities and personalities (KSAP). The study involved focus group discussion (FGDs), a pilot study and the distribution of questionnaires. Importance-performance analysis (IPA) was used to assess the managers perceptions of these graduates. It was determined that HEIs producing technical graduates should target the improvement of implicit and tacit knowledge of technical students, maintain their (HEIs) current efforts to provide them with hard skills, soft skills, intellectual abilities and personality development. They should also reduce their current efforts to improve the physical abilities of technical students when relating the relevance of the existing technical education curriculum to current market needs. Producing sustainable technical graduates through this innovative industry driven approach will improve perceived problem areas in the technical education curriculum encompassing the four dimensions. 2017 American Scientific Publishers All rights reserved.